'Half alive, half dead' boys: sexuality and censorship in Wilfred Bion's 'The long weekend'. Issue 2 (4th May 2021) - Smith, Tim
ABSTRACT: This paper traces Wilfred Bion's disrupted sexual development from young child in India to schoolboy in England, as described in his autobiography 'The long weekend'. It discusses the meaning of Bion's baffling descriptions of sex at his Hertfordshire boarding school, where he puts the topic front and centre, yet affords it a peculiar kind of censorship, via an understanding of the moral and religious way that boys' sexuality in segregated boarding schools was viewed and dealt with during the Edwardian era. The paper explores the stifling impact this had on Bion's creativity. It also describes how Bion's personal qualities of courage, his capacity to observe and his interest in the truth, helped to counterbalance the destructiveness that had led him to reject relationships. The emotional deprivation, bleakness and aggression he recalls are viewed as being of interest to child psychotherapists working with contemporary adolescent sexual difficulties.